Hybrid Fully Generalized Spatial Modulation for mmWave Vehicular Communications - Ali Mohamed Hashim, Sheemaa; Dziyauddin, Rudzidatul Akmam; Mohd Izhar, Mohd Azri; Prasetya, Budi (International Journal of Integrated Engineering, 2024)
This article addresses the challenge of achieving high spectral efficiency (SE) in millimeter wave (mmWave) vehicular communications. Traditional approaches using conventional multiple input multiple output (MIMO) systems face complexity and cost issues, compounded by the rapid mobility of vehicles. A promising technique, Fully Generalized Spatial Modulation (FGSM), has been proposed for enhancing SE with low complexity. However, its application in vehicular environments remains limited. To fill this gap this article introduces a novel approach termed Hybrid-Fully Generalized Spatial Modulation (H-FGSM) for vehicular communication. H-FGSM not only boosts spectral efficiency and achievable data rates but also incorporates hybrid beamforming at the transmitter to enhance vehicle connectivity. Our numerical analysis demonstrates that the proposed H-FGSM outperforms baseline schemes, achieving higher data rates and improvements in system error rates, as exhibiting a 2 dB improvement in Bit Error Rate (BER) performance and a 30 bits per channel use (bpcu) disparity in attainable achievable data rate when the Signal-to-Noise Ratio (SNR) is higher.